RASTOROPSHA (SILYBUM MARIANUM L.) THE USE OF BIOPREPARATIONS IN CULTIVATING - S. X. Babadjanova; Sh. T. Matsafayeva; N. A. Xudayberganov (Web of Journals Publishing, 2024)
The article scientifically establishes a biotechnological strategy for using microbial preparations that increase resistance to the conditions of Khmer Rouge and help in the development and growth of medicinal plant Silybum marianum L. The use of "Earth-M" and "Earth ointment" biopreparations is shown to be good, and at the end of the article the conclusions are presented.
Keywords: microbial preparation, Earth ointment, Earth-M, Silybum marianum L., medicinal plant, biological fertilizer, soil, mineral boys.